Vulnerability Index of the Congo Monkey (Alouatta Palliata Palliata) from the Vision of Sustainable Development for its Conservation (Revista Rupturas, 2024)
The vulnerability assessment of the species of howler monkey (Alouatta palliata palliata) in Playa Hermosa, Guanacaste, Costa Rica was possible through the application of a Vulnerability Index (VI) that integrates the 4 axes of Sustainable Development. Vulnerability for this species was found to be high (63%). Mainly in the economic and political-institutional criteria, while the social and environmental contribute 50% [S (14%) + A (15%) + E (17%) + PI (17%) = IV (63%)]. In this way, the lines of action should focus on the implementation of policies and management plans that incorporate the howler monkey as a focal species and infrastructure intervention present in its habitat, such as power lines and roads.
Keywords: Vulnerability Index; Sustainable Development; Alouatta palliata palliata; howler monkey